2017
DOI: 10.1038/s41598-017-05156-9
|View full text |Cite
|
Sign up to set email alerts
|

Metal Nanoclusters with Synergistically Engineered Optical and Buffering Activity of Intracellular Reactive Oxygen Species by Compositional and Supramolecular Design

Abstract: Metal nanoclusters featuring tunable luminescence and high biocompatibility are receiving attention as fluorescent markers for cellular imaging. The recently discovered ability of gold clusters to scavenge cytotoxic reactive oxygen species (ROS) from the intracellular environment extends their applicability to biomedical theranostics and provides a novel platform for realizing multifunctional luminescent probes with engineered anti-cytotoxic activity for applications in bio-diagnostics and conceivably cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…Luminescent superstructures based on quantum metal clusters have been recently studied for their peculiar emission properties, which, coupled with an extremely high biocompatibility, pushed their evaluation as optical probes for imaging (47). Moreover, considering noble metal clusters, preliminary assays indicated a remarkable anti-cytotoxic activity of these materials (45). We recently demonstrated that in the case of Au8 gold clusters superstructures (Au8-pXs), this effect was correlated to a ROSscavenging ability of the material (44), which could be linked to the reported catalytic effect of Au nanostructures on chemical and photochemical reactions involving oxygen (46,48).…”
Section: Ros Buffering Effect Of Au8-pxsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescent superstructures based on quantum metal clusters have been recently studied for their peculiar emission properties, which, coupled with an extremely high biocompatibility, pushed their evaluation as optical probes for imaging (47). Moreover, considering noble metal clusters, preliminary assays indicated a remarkable anti-cytotoxic activity of these materials (45). We recently demonstrated that in the case of Au8 gold clusters superstructures (Au8-pXs), this effect was correlated to a ROSscavenging ability of the material (44), which could be linked to the reported catalytic effect of Au nanostructures on chemical and photochemical reactions involving oxygen (46,48).…”
Section: Ros Buffering Effect Of Au8-pxsmentioning
confidence: 99%
“…Au8-pXs is a novel highly biocompatible material based on gold quantum clusters, i.e. sub-nanometer structures made from few units to hundred gold atoms, which possess excellent ROS scavenger therapeutic potential (44,45), probably related to their demonstrated catalytic activity (46). In our study, we examined the effect of Au8-pXs treatment on bone marrow-derived mesenchymal stem cells (BMSCs) from FRDA patients and found that Au8-pXs not only acts as an antioxidant to relieve the oxidative stress improving the mitochondrial function, but also rescue the autophagy flux and increases FXN protein levels, which would be the fundamental resolution for FRDA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Химические активные соединения кислорода (reactive oxygen species, ROS) играют важную роль в фотокаталитических процессах и антибактериальной активности материалов [2,[6][7][8][15][16][17][18][19], и разрабатываются устройства, обеспечивающие формирование этих соединений кислорода в газовых потоках [20,21]. Высокоэффективные мембраны, содержащие наночастицы, разрабатываются для систем очистки воды [22,23].…”
Section: Introductionunclassified
“…Gold nanoclusters (AuNC), composed of several atoms to several hundred unequal gold atoms, have attracted considerable interest because of their intriguing aesthetic structures and desired photophysical properties [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. Their ultrasmall size (<2 nm), which is comparable to the Fermi wavelength of electrons, hampers the surface movement of valence electrons, giving rise to discrete electronic transitions and resulting interesting molecular properties, e.g., molecular chirality, HOMO–LUMO transitions and photoluminescence [15].…”
Section: Introductionmentioning
confidence: 99%